Designand implementation of wearable single chip system for sensing, processing and transmitting human gesture and motion data - Snehith.H, Venkata; Ratna D, Likita; Shameem, Syed (International Journal of Engineering and Technology, 2018)
Our work aims at the design of wearable electronic modules that can be assembled as systems for sensing, processing, transmitting, actuating and mimicking human hand gestures and movements, to be used in various robotic, educational, military, medical, industrial, general and hobby applications, the secondary focus of our work is reducing the cost, complexity and assembly of such systems, which are already being used by research centers, laboratories and high-class industries all over the world while the primary objective is to bring these systems down to customizable modular components which could be assembled and combined the way the user wishes to and needs them to be, thereby bringing these concepts closer to a wider range of students, enthusiasts and hobbyists making it easy for them to understand and comprehend these concepts even at the beginner level. In our project, we used commonly available piezo-resistive materials and other household items to make force, pressure, stress, strain and bend sensors and appended them to an Inertial measurement unit, a microcontroller and a wireless transceiver all embedded onto a single chip, to create a simple sensing mechanism that could be worn on a human hand to sense, process and transmit the gestures for actuating and mimicking applications.